A new species and new records of Chumma (Araneae, Macrobunidae) from South Africa - Marusik, Yuri M.; Haddad, Charles R. (Pensoft Publishers, 2024)
A new species of the genus 𝘊𝘩𝘶𝘮𝘮𝘢 Jocqué, 2001, C. 𝘧𝘰𝘰𝘳𝘥𝘪 𝐬𝐩. 𝐧𝐨𝐯., is described from the Western Cape, South Africa. New distribution records for 𝘊. 𝘣𝘪𝘤𝘰𝘭𝘰𝘳 Jocqué & Alderweireldt, 2018, 𝘊. 𝘧𝘰𝘭𝘪𝘢𝘵𝘢 Jocqué & Alderweireldt, 2018 and 𝘊. 𝘨𝘢𝘴𝘵𝘳𝘰𝘱𝘦𝘳𝘧𝘰𝘳𝘢𝘵𝘢 Jocqué, 2001 are presented. The genus is recorded from the Northern Cape Province for the first time, extending its range extensively to the northwest by approximately 450 km. The distribution of all 𝘊𝘩𝘶𝘮𝘮𝘢 species is mapped.
Keywords: Amaurobiidae; Aranei; Chummidae; Forest; Fynbos; Spider